Processos externalizadores: normas, práticas e tecnologias de gênero no universo transmasculino no Ceará - Lemos, Kaio Souza (2020)
The externalizing processes encompass a number of transient possibilities related to the body intertwined in the process that we call “bodily and sexual externalization” that transsexual people go through during their transits. In view of the presumed, the simple fact of creating the “guidelines for comprehensive care” does not meet or correspond to the desires and desires of these necessary actions, mainly the right to health and respect for gender identity through the social experiences that are the most desired assets by the trans population. In order to understand the functioning of the transsexualizing device, it is necessary to look carefully at the ordinances that value this process. Initially Ordinance no. 1,707, of August 18, 2008 (BRASIL, 2008), the Ministry of Health implemented the technical guidelines for the "Transexualizador Process in the Unified Health System" (SUS). This process is composed of techniques and procedures related to health, which is also very involved in the processes of externalization and bodily and sexual changes of trans people. These processes are not discussed, analyzed and created thinking only in line with “Guidelines for comprehensive care”, but rather necessary practices that guarantee the right to health, social inclusion and the experiences of trans people figuring the recognition of the desire to live, valuing their subjectivity. In this study proposal, I intend to make an ethnographic analysis dealing with the non-existence of the transsexualizing clinic, the difficulty in obtaining specialized medical monitoring by the public health network (SUS) for people in the process of transsexualization (or who wish to start it) in the state of Ceará, in addition to the constant violations of fundamental rights suffered by the trans population in the State of Ceará.